Delayed access to innovative medicines in Romania: a comprehensive analysis of the reimbursement processes (2015–2024) - Radu, Constantin; Serban, Diana Elena; Chiriac, Nona Delia (Frontiers in Public Health, 2025)
IntroductionRomania’s reimbursement framework for innovative medicines relies on health technology assessments (HTAs) resulting in unconditional or conditional decisions. Although conditional decisions aim to manage financial uncertainty via Cost-Volume (CV) agreements, anecdotal evidence points to growing delays and a growing backlog of indications waiting to be reimbursed. This study is the first to systematically quantify these delays and assess their evolution over time.MethodsWe analyzed all publicly available full HTA reports (2015–2024) from Romania’s National Drug Agency. Each indication was classified by HTA decision (unconditional, conditional, or negative) and reimbursement status. Descriptive analyses included mean and median durations for HTA and reimbursement processes. A Kaplan–Meier survival analysis compared time-to-reimbursement between conditional and unconditional indications. Finally, we fit a simple linear model (2022–2024) to project future backlog growth under current policies.ResultsOut of 613 full HTA reports covering 666 indications, 44% were conditionally approved, 42% unconditionally, and 14% received a negative decision; oncology accounted for ~40% of all indications. The HTA process (submission to decision) improved considerably, with mean durations nearly halving from 208 days in 2020 to roughly 100 days in 2024. Despite these improvements, the mean time from HTA decision to reimbursement rose from 222 days in 2020 to 461 days in 2024 overall, with conditional decisions taking on average 274 more days than unconditional ones in 2024. Kaplan–Meier analysis showed that by 24 months post-HTA decision, 98.3% of unconditional indications were reimbursed, compared to only 60.1% of conditional indications. Meanwhile, the backlog of unreimbursed indications increased from 47 in 2022 to 146 in 2024, and linear projections suggest it could reach 247 by 2026 under the current system.DiscussionDespite some efficiency gains in the HTA evaluation stage, Romania’s conditional reimbursement pathway remains hampered by tight budgets and administrative hurdles, prolonging patient inaccessibility—particularly in oncology, where timely treatment is critical. Strengthening administrative capacity, diversifying Managed Entry Agreement (MEA) models, and integrating new digital tools could help address these bottlenecks. Without substantial reforms, the backlog will continue growing, limiting patients’ timely access to innovative therapies.